Effecting Shear Span Ratio on High Strength Fiber Reinforced Concrete Deep Beams with Circle Openings - Sahere, Hamed Salem; Abdalimam, Mazin; Chkheiwer, Aqeel Hatem (Basrah Journal for Engineering Sciences, 2019)
This study investigates the effect of the shear span-to-effective depth ratio (a/d) on the behavior of high-strength steel fiber–reinforced concrete deep beams without stirrups containing circular web openings. A circular opening of 12.6 cm diameter was positioned at the center of the shear span, and beam performance was evaluated in terms of crack patterns, load–deflection response, and stress–strain behavior. Four specimens were tested experimentally. The control specimen consisted of a solid deep beam without openings and without steel fibers, while the remaining three specimens were reinforced with 1% steel fibers and included circular openings. All specimens were reinforced with 2Ø12 mm top bars, 3Ø16 mm bottom bars, and two stirrups at the supports to prevent local failure. The beams had different shear span ratios (a/d = 0.75, 1.0, and 1.5) and corresponding total lengths of 1025 mm, 1200 mm, and 1550 mm, respectively. All specimens were simply supported and subjected to two-point loading. The experimental results revealed that the optimal shear span ratio for maximum performance was a/d = 0.75 when combined with 1% steel fiber reinforcement. In addition, the ultimate strength of beams with circular openings decreased as a/d increased, with a strength increase of approximately 5.48% at a/d = 0.75 compared with a/d = 1.0.